mSphere of Influence: Venturing outside the biology canon with sex and gender - Victoria Prieto-Echagüe (mSphere)
ABSTRACT Victoria Prieto-Echagüe works in the field of signaling by primary cilia, adipogenesis, and obesity. In this mShpere of Influence article, she reflects on how gender studies, feminism, and societal movements such as #metoo may inform all areas of biomedical and health research. She describes how they inspired her to incorporate sex as a biological variable (SABV) principle to her research exploring sex-specific mechanisms in obesity and metabolic diseases and argues that incorporating SABV is crucial for advancing precision medicine and addressing healthcare inequities.